Attitudes Toward Digital Content on Religious Tolerance - Mualim; Aulia Naufal (Esensia: Jurnal Ilmu-Ilmu Ushuluddin)
In the digital era, religious expression among adolescents is increasingly shaped by content shared on digital platforms. Social media has become a primary source of religious reference for college students, influencing their attitudes toward religious moderation and tolerance. This study quantitatively examines the relationship between digital content on religious tolerance and students’ attitudes, particularly in different academic settings. Drawing on mediatization theory and digital religion theory, this research offers a novel contribution by empirically exploring a relationship that has received limited attention in prior studies. A total of 460 college students from Kuningan, Indonesia, participated in the study, evenly divided between religious and non-religious campuses. Data were collected through a structured questionnaire using purposive sampling. Descriptive statistics, reliability and validity tests, and multiple regression analysis were conducted using SPSS. The results show that students from religious campuses exhibit higher levels of religious moderation and tolerance compared to those from non-religious campuses. These findings suggest that religious academic environments may play a more effective role in fostering these values. The study underscores the importance of integrating religious tolerance into digital media engagement and incorporating religious values into non-religious campus settings to help mitigate the spread of extremism and intolerance online.